2016
DOI: 10.13057/biodiv/d170242
|View full text |Cite
|
Sign up to set email alerts
|

Biological characteristics on three demersal fish landed in Tegal, north coast of Central Java, Indonesia

Abstract: Abstract. Nugroho D, Patria MP, Supriatna J, Andrianto L. 2016. Biological characteristics on three demersal fish landed in Tegal, north coast of Central Java,. Java Sea has a potential marine biodiversity that has been harvested since years. Demersal fish resources is one of the targeted species by Danish seine fisheries operated in North coast of Java. To support on developing conservation and management measures, an observation on species composition, length frequencies and maturity stages were carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 11 publications
0
9
0
6
Order By: Relevance
“…Aglen et al (1981) informed that P. longimanus occurred in the waters of less than 60 m in Peninsular Malaysia. Nugroho et al (2016) indicate that the species were more abundant in the depth of more than 20 m in western part of the Java Sea.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Aglen et al (1981) informed that P. longimanus occurred in the waters of less than 60 m in Peninsular Malaysia. Nugroho et al (2016) indicate that the species were more abundant in the depth of more than 20 m in western part of the Java Sea.…”
Section: Introductionmentioning
confidence: 84%
“…This has been a growing concern in this fisheries for years. The persistence of high landing of juveniles and lower proportion of mature adults in Scottish seine fisheries suggests that large fish abundance was under pressure (Nugroho et al 2016). As the fish is a typically sedentary species it is predicted that the exploitation rates have a negative impact on current stock status, when the fishing mortality exceed half of the mature fish, the stock status fall below precautionary limits (Vasilakopoulos et al 2011) Gonadosomatic index (GSI) Gonadosomatic index (GSI) analysis indicated that monthly average slightly fluctuated except for May 2015 which give a high index.…”
Section: Maturitymentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 12,969 specimens were taken for length frequency distribution, among them, 2,038 fish specimens were collected for biological observations (688 Priacanthus tayenus, 587 Scolopsis taenioptera and 763 Upeneus sulphureus) belong to three different families of Priacanthidae, Nemipteridae and Mullidae. The biological characteristics of these species were previously described elsewhere (Nugroho et al 2016). Fish length was measured in mm, while weight measurement is in grams.…”
Section: Methodsmentioning
confidence: 99%
“…Among eight provincial coastal waters surrounding Java Sea, 93% of these species landed in the north coast of central Java. Previous studies on biological characteristics of dominant species in the north coast of Java have shown that landing is dominated by small size of fish and medium tropic level fisheries, therefore, the exploitation of the demersal fish species is suggested to be at risk (Nugroho et al 2016).…”
Section: Introductionmentioning
confidence: 99%